Design Of Transaction Information System And Data Storage At Ahza Abadi Pharmacy In Makassar - Nurul Chairany; Rendy Aryandi; Anis Saleh; Muhammad Nusran (Journal of Industrial System Engineering and Management, 2022)
Ahza Abadi Pharmacy Makassar is one of the businesses in the field of drug sales. In some data processing processes, there are problems due to manual recording of data into an archive book so that unwanted things often happen, such as what happened in the record book or damage to the book, while selling and buying transactions carried out without evidence. transactions thatoften occur between employees and buyers. This study aims to create an information system design to overcome problems in conducting transactions and storing data so that employees can easily input data and print receipts for buyers as proof of transactions. This research uses the prototype method in designing information systems that focus on the presentation of input and output in the form of use case diagrams and activity diagrams. The results of this study are the design of a transaction information system and data storage into a transaction information system and data storage